The art of 64-bit assembly. - Hyde, Randall (No Starch Press, 2022)
"A thorough guide to writing high-performance programs in 64-bit assembly language using the Microsoft MASM assembler. Programmers that can code in a high-level language will learn about memory access, numeric conversion, bit manipulation, and managing complex projects"--